2016
DOI: 10.3847/0004-637x/827/1/26
|View full text |Cite
|
Sign up to set email alerts
|

The Phase Coherence of Interstellar Density Fluctuations

Abstract: Studies of MHD turbulence often investigate the Fourier power spectrum to provide information on the nature of the turbulence cascade. However, the Fourier power spectrum only contains the Fourier amplitudes and rejects all information regarding the Fourier phases. Here, we investigate the utility of two statistical diagnostics for recovering information on Fourier phases in ISM column density maps: the averaged amplitudes of the bispectrum and the phase coherence index (PCI), a new phase technique for the ISM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The spatial power spectrum, defined as the Fourier transform of the two-point autocorrelation function, does not include information about phase. Burkhart et al (2009) introduced the bispectrum as a tool for probing nonlinear wave-wave interactions in a turbulent energy cascade (see also Burkhart & Lazarian 2016). They showed that MHD wave modes produce stronger turbulence correlations than that of purely hydrodynamical perturbations.…”
Section: Bispectrum/bicoherencementioning
confidence: 99%
“…The spatial power spectrum, defined as the Fourier transform of the two-point autocorrelation function, does not include information about phase. Burkhart et al (2009) introduced the bispectrum as a tool for probing nonlinear wave-wave interactions in a turbulent energy cascade (see also Burkhart & Lazarian 2016). They showed that MHD wave modes produce stronger turbulence correlations than that of purely hydrodynamical perturbations.…”
Section: Bispectrum/bicoherencementioning
confidence: 99%
“…The 3PCF has had significant success in cosmology describing the non-Gaussian distribution of galaxies (Slepian et al (2017a,b), and references therein). The 3PCF (Portillo et al 2018) and bispectrum (Burkhart et al 2009;Burkhart & Lazarian 2016) have also been applied to MHD simulations and show some discriminatory power, but interpretation of these higher order statistics remains difficult.…”
mentioning
confidence: 99%
“…For example,Burkhart & Lazarian (2016), analysing numerical simulations of isothermal Scheme of descriptors used to quantitatively characterize the MFS in this work, and introduced in the text. The example MFS (green curve) is the one of the 224 map at 250 µm, also contained inFigure 5.…”
mentioning
confidence: 99%